Foreign-language skills of student paramedics studying undergraduate Paramedic Science in the UK: a nationwide cross-sectional exploratory study. - Finney, Owen (British Paramedic Journal, 2025)
Introduction: Communication is essential in healthcare, but language barriers between patients and clinicians can hinder care quality, especially as the UK sees an increasing number of non-native English speakers. The 2021 UK census revealed that 5.1 million people do not speak English as a first language, with many having limited or no proficiency. Despite these trends, little research has been carried out to explore the experiences of these individuals in pre-hospital care, where language challenges often arise. UK paramedic education includes communication training, but foreign-language learning is not part of most curricula. Some universities offer optional language modules, yet there is no data on how many paramedics or student paramedics speak additional languages. Clinicians with foreign-language skills could enhance patient satisfaction and reduce communication barriers, but there is a lack of pre-hospital evidence in this area. This exploratory study aimed to capture the foreign-language skills of student paramedics in the UK, addressing a gap in the literature and laying the groundwork for future research. Methods: This exploratory study employed a quantitative, cross-sectional design using an online survey distributed to student paramedics across 24 higher education institutions in the UK during April and May 2024. The survey captured demographic data and language competencies, with descriptive statistics used for analysis. Results: Out of 105 respondents, 73 were female (69.5%), and the mean age was 23.65 (± 8.25). Over half (53.3%) reported proficiency in at least one foreign language, predominantly languages spoken in Europe, such as French (48.2%), Spanish (35.7%) and German (21.4%). Most respondents had beginner-level skills (64.3%), with no formal language training in their programmes. However, 57.7% expressed interest in studying an optional foreign-language module. Conclusion: This study found that over half of student paramedics possess foreign-language proficiency. The majority of the sample indicated a desire to study a foreign language if given the opportunity during their paramedic training. Given the increasing linguistic diversity in the UK, integrating language modules into paramedic education could enhance patient care and satisfaction. Further research is needed to explore the feasibility of such training and its impact on pre-hospital care outcomes for non-native English speakers.